Developmental Variation of Indian Thermophilic Variety of Scuttle Fly Megaselia (Megaselia) scalaris (Loew, 1866) (Diptera: Phoridae) on Different Substrates. (4th July 2016) - Chakraborty, Abesh; Naskar, Atanu; Parui, Panchanan; Banerjee, Dhriti
Abstract : The scuttle flies (Diptera: Phoridae) are important in forensic dipterology, because of their necrophagous habit. They are amongst the first wave of insects visiting human corpses in mechanically barricaded environments; hence their immature stages are generally used for estimation of PMI. The effect of different substrates commonly used for developmental studies was studied to analyze the variation of growth of the thermophilic variety of Megaselia (M.) scalaris prevalent in India on GDM, EDM, and SMS (n = 3 ). One approach of PMI estimation depends on larvae collected from the crime scene and comparing them with reference data derived from larval rearing to establish PMI. Results showed that there was a significant variation in avg. length (F ( 2, 111 ) = 15.79873, p = 0.000000917 ), width (F ( 2, 111 ) = 14.60528, p = 0.00000234 ), and biomass (F ( 2, 111 ) = 37.01727, p = 0.000000000000482 ) of the immature stages in the three media and the larvae grow maximally in the SMS medium. The results of the present study thus provide baseline data on the growth and developmental pattern of the Megaselia (M.) scalaris, which can be utilized in conjunction with specific geoclimatic reference data, for forensic entomological studies and also for using the phorid as a biocontrol agent of pestiferous insects.